Aspek-aspek Kejiwaan dan Motivasi Manusia dalam Konsepsi Islam - Ratnawati Ratnawati (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The discription of human’s psyche and motivation was besides discribed by general psychology it was also done in the Islamic psychology. Human psyche and motivation in general psychology is more emphasized on the worldly interests, meanwhile the psyche and motivation in Islam bisides containts the worldy interests it also includes the religious belief to firmly believe in the truth of Islamic doctrines. These points of differences is more caused by the opinion paradigm used. The object of general psychology is the real facts, meanwhile in the Islamic psychology besides views the materials also perceives the immaterials. The Islamic psychology containts the elements related to religious preferences for the shake of religious or belief interests, meanwhile it is less or nothing in general psychology. The aspect of religious is the special charecteristic of Islamic psychology compared with general psychology or others.